Shari'ah values for modern societies: analysis of contents and contexts - Zakariyah, Luqman (Routledge Taylor & Francis Group, 2013)
Many approaches have been explored to explain the concept of Shari‘ah and its values in classical and modern literatures. Some approaches are meant to juxtapose Shari‘ah and its values with other concepts, an attempt that suggests a sense of clash of civilization and advocates superiority of one legal system over another and somewhat echoes egoism and incompatibility (Kelly, 2010; An-Na‘im, 2008).